Steps to Build Your Own Niche Market - Husnul Khotimah; Farida Febriati (Green Economics: International Journal of Islamic and Economic Education, 2025)
Digital transformation in the Industry 4.0 era has accelerated changes in consumer behavior and intensified competition in online markets. Under heterogeneous and increasingly saturated conditions, mass-marketing approaches become less effective, making niche market strategies more relevant as a path to differentiation. This article aims to formulate a systematic framework for independently building a niche market in the digital era through a synthesis of academic literature and a practical social-media case. The study uses a conceptual literature review integrating niche marketing theory, niche success characteristics, and social media marketing dynamics. The review indicates that effective niche market development follows sequential stages: (1) identifying specific market needs/problems, (2) designing a relevant product/service solution, (3) sharpening the target into a clearly defined niche, (4) formulating a unique selling point (USP) and value proposition, (5) conducting small-scale validation through a portfolio/MVP, (6) executing social media marketing, (7) maintaining consistent content and digital branding, and (8) performing continuous adaptive evaluation. The @foodish_mks case reinforces that content consistency and social-media utilization act as key mechanisms linking digital marketing intensity to niche success. This article contributes a cross-sector niche-building roadmap aligned with algorithmic, community-based digital platforms, and proposes a testable hypothesis model (H1–H6) for future empirical validation.